2022
DOI: 10.1093/gerona/glac192
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Links of Daily Sleep Quality and Duration With Pain and Self-rated Health in Older Adults’ Daily Lives

Abstract: Background Sleep and health perceptions such as self-ratings of pain and health are closely linked. However, the temporal ordering of such associations is not well understood and it remains unclear whether sleep quality and sleep duration show similar or differential associations with health perceptions. Methods We used ecological momentary assessment data from 123 young-old (66-69 years, 47% women) and 47 old-old adults (84-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Corresponding to what has been reported in a study among older adults [81], the current study contributes to the body of knowledge indicating that self-rated health is an important predictor of sleep quality among university students. In our regression model, we found that perceived stress was a significant predictor of sleep quality.…”
Section: Health-related Indicatorssupporting
confidence: 72%
“…Corresponding to what has been reported in a study among older adults [81], the current study contributes to the body of knowledge indicating that self-rated health is an important predictor of sleep quality among university students. In our regression model, we found that perceived stress was a significant predictor of sleep quality.…”
Section: Health-related Indicatorssupporting
confidence: 72%
“…Another study has also found that sleep deficiency, particularly insomnia and poor sleep quality, might modify the effectiveness of psychological treatments for CP ( 45 ). If participants report better sleep quality, they will have less pain and better self-rated health on the following day ( 46 ). Improving sleep quality is an important approach to reduce the CP burden ( 47 ).…”
Section: Clinical Research On the Relationship Between Chronic Pain A...mentioning
confidence: 99%